Alternate Day Fasting Improves Endothelial Function in Type 2 Diabetic Mice: Role of Adipose-Derived Hormones - Cui, Jian; Lee, Sewon; Sun, Yan; Zhang, Cuihua; Hill, Michael A.; Li, Yuhang; Zhang, Hanrui (Frontiers in Cardiovascular Medicine, 2022)
Introduction Intermittent fasting, including alternate day fasting (ADF), has grown in popularity as it can produce clinically significant metabolic benefits and is often considered to be easier to adhere to than other types of diets such as chronic calorie restriction. However, the effects of ADF on diabetes-associated vascular dysfunction, and the role of adipose-derived hormones, i.e., adipokines, in mediating its effects, remain largely unknown. Objective We aimed to test the hypothesis that ADF protects against diabetes-associated endothelial dysfunction, at least partly through modulating adipokine profiles. Methods Control mice (m Leprdb) and diabetic mice (Leprdb) were treated with 12-weeks of ADF. Glucose metabolism, endothelial function, and adipokine profile were assessed. Results ADF reduced fasting blood glucose level and homeostatic model assessment for insulin resistance (HOMA-IR), and improved insulin sensitivity. ADF improved endothelium-dependent vasorelaxation of small mesenteric arteries (SMA) of Leprdb mice. The improvement in endothelial function was largely attenuated by incubation with the nitric oxide synthase inhibitor, L-NAME. These ADF-induced metabolic and vascular benefits were accompanied by increased circulating adiponectin. Adenovirus-mediated adiponectin supplementation improved endothelial function in Leprdb mice, supporting endothelial protective roles in diabetes-associated endothelial dysfunction. Protein tyrosine nitration is a post-translational modification that serves as a marker of oxidative stress. Nitrotyrosine protein levels in SMA and mesenteric adipose tissue (MAT) were elevated in Leprdb mice. ADF reduced nitrotyrosine protein in SMA, but not in MAT, of Leprdb mice. Conclusion ADF exerts metabolic and endothelial protective benefits. The improvement of endothelial function was partly mediated by increased adiponectin, representing an important mechanism for the beneficial vascular effects resulting from ADF.